Intestinal regulation of urinary sodium excretion and the pathophysiology of diabetic kidney disease: a focus on glucagon‐like peptide 1 and dipeptidyl peptidase 4. Issue 9 (26th August 2014) - Vallon, Volker; Docherty, Neil G.
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? This review describes how hyperglycaemia and attendant increases in proximal tubular growth and sodium reclamation form the mechanistic basis for the tubular hypothesis of hyperfiltration and nephropathy in the kidneys of patients with diabetes. The review highlights how signals arising from the gastrointestinal tract may be capable of modulating this response and how pharmacological enhancement of these signals may ameliorate the progression of diabetic kidney disease. What advances does it highlight? The review highlights the potential of glucagon‐like peptide 1 analogues, glucagon‐like peptide 1 receptor agonists and dipeptidyl peptidase 4 inhibitors to exercise renoprotective effects in diabetes independent of their classical effects on endocrine pancreas. The tubular hypothesis of glomerular filtration and nephropathy in diabetes is a pathophysiological concept that assigns a critical role to the tubular system, including proximal tubular hyper‐reabsorption and growth, which is relevant for early glomerular hyperfiltration and later chronic kidney disease. Here we focus on how harnessing the bioactivity of hormones released from the gut may ameliorate the early effects of diabetes on the kidney in part by attenuating proximal tubular hyper‐reabsorption and growth. The endogenous tone of the glucagon‐like peptide 1 (GLP‐1)/GLP‐1 receptor (GLP‐1R) system and its pharmacological activation are nephroprotective in diabetes independent of changes in blood glucose. This is associated with suppression of increases in kidney weight and glomerular hyperfiltration, which may reflect, at least in part, its inhibitory effects on tubular hyper‐reabsorption and growth. Inhibition of dipeptidyl peptidase 4 (DPP‐4) is also nephroprotective independent of changes in blood glucose and involves GLP‐1/GLP‐1R‐dependent and ‐independent mechanisms. The GLP‐1R agonist exendin‐4 induces natriuresis via activation of the GLP‐1R. In contrast, DPP4 inhibition increases circulating GLP‐1, but drives a GLP‐1R‐independent natriuretic response, implying a role for other DPP‐4 substrates. The extent to which the intrarenal DPP‐4/GLP‐1 receptor system contributes to all these changes remains to be established, as does the direct impact of the system on renal inflammation.